Reconstruction of the Meaning of Lakhõmi Using Pope Francis’ Perspective in Fratelli Tutti - Sarumaha, Pankrasia Niasti; Borgias, Fransiskus (MELINTAS, 2025)
Amid the complexities of contemporary social realities marked by inequality, discrimination, and exclusion, the values of local culture remain vital in shaping the identity and social structures of communities. Within the Nias cultural tradition, the concept of Lakhõmi is esteemed as a symbol of human dignity and honour. However, in practice, this value is often entangled with patriarchal social structures that reinforce male dominance, thereby contributing to gender disparities, particularly in the status and roles of women within Nias society. In contrast, Pope Francis, in his encyclical Fratelli Tutti, offers profound insight into the concept of universal fraternity. This study aims to re-examine the meaning of Lakhõmi by engaging in a dialogical encounter with the values articulated in Fratelli Tutti. Through a literature-based approach, this study explores the potential for reconstructing Lakhõmi in ways that affirm its relevance within an ever-evolving social context. It is hoped that such an endeavour will not only preserve the noble values embedded in the local culture but also contribute to the formation of a more just, equitable, and harmonious society.